Petrogenesis and geodynamic implications of the Mid-Triassic lavas from East Kunlun, northern Tibetan Plateau. (1st June 2015) - Li, Xiaowei; Huang, Xiongfei; Luo, Mingfei; Dong, Guochen; Mo, Xuanxue
Highlights: The Haishigou volcanic lavas belong to part of the Middle Triassic Naocangjiangou Formation. The Haishigou volcanic rocks show geochemical affinities similar to those rocks which formed in the continental arc setting. East Kunlun was a continental arc during the Middle Triassic. Abstract: Lying in the northern margin of the Tibetan Plateau, the East Kunlun Orogenic Belt (EKOB) is characterized by widespread of the late Permian to Late Triassic magmatic rocks. In order to better understand magma genesis and evolution during the waning stage of the Paleo-Tethyan oceanic subduction and subsequent collision, we present zircon U–Pb dating and Lu–Hf isotopes, whole-rock major and trace elements, and Sr–Nd isotope data for the Triassic volcanic lavas in the Haishigou area of the EKOB, northern Tibet. Lithologically, the Haishigou volcanic lavas are mainly composed of dacites and rhyolites. The LA–ICP–MS zircon U–Pb analyses for rhyolites have shown that the Haishigou volcanic rocks formed during the Middle Triassic with ages of ca. 244–245 Ma. The Haishigou volcanic lavas actually belong to part of the Middle Triassic Naocangjiangou Formation, rather than the Late Triassic Elashan Formation. Geochemically, Haishigou volcanic lavas have SiO2 = 60.31–76.19 wt% and K2 O = 2.60–4.18 wt%, placing them in high-K calc-alkaline series. These lavas are characterized by enrichment in some large-ion lithophile elements (e.g., Rb, K and Pb) and light rare earth elements and depletion in some high field strength elements (e.g., Nb, Ta, and Ti), with geochemical affinities to those rocks forming in a continental or an oceanic arc setting. All the volcanic rocks exhibit high initial 87 Sr/ 86 Sr ratios (0.70614–0.70841) and moderately negative ε Nd ( t ) values (−5.9 to −4.3) that imply a continental rather than oceanic type magma source. The rhyolites in the Haishigou volcanics exhibit moderately negative to slightly positive ε Hf ( t ) values (−4.2 to 1.4). Combined with their zircon Hf two-stage model ages of 1187–1538 Ma and whole-rock Nd two-stage model ages of 1.37–1.38 Ga, it can be inferred that the crustal growth of East Kunlun occurred during the Mesoproterozoic, making them similar in age to the lower crust metamorphic basement beneath the EKOB (i.e., the Xiaomiao Group). We suggest that the Haishigou dacites were generated by partial melting of the mafic lower crust beneath the EKOB with addition of a mantle-derived mafic component and that the rhyolites were produced by fractional crystallization from a dacitic parent. Taking into account the Late Permian to Triassic geological record from the EKOB and surrounding regions, we argue that the Middle Triassic volcanic rocks in the Haishigou area erupted during the northward subduction of the Paleo-Tethyan oceanic plate. Consequently, the timing of closure of the Paleo-Tethyan Ocean just south of the EKOB is no earlier than the Middle Triassic.